Spinal cord compression as tumor onset: an unusual case report of Hodgkin lymphoma in a teenager - Giulia Salomone; Milena La Spina; Giuseppe Belfiore; Gregoria Bertuna; Laura Cannavò; Stefano Catanzaro; Salvatore D'Amico; Mariaclaudia Meli; Andrea Musumeci; Lucia Salvatorelli; Maria Grazia Scuderi; Corrado Spatola; et al. (BMC, 2021)
Abstract Background Spinal cord compression (SCC) is an uncommon, severe complication of Hodgkin lymphoma (HL), occurring in 0.2% of cases at the onset and in 6% during disease progression. We present a teenager with SCC with clinical onset of HL; her pre-existing neurological abnormalities covered the presence of an epidural mass, which could have misled us. Case presentation A 13-year-old girl presented with a three-month history of lower back pain and degrading ability to walk. She suffered from a chronic gait disorder due to her preterm birth. A magnetic resonance imaging of the spine revealed an epidural mass causing collapse of twelfth thoracic vertebra and thus compression and displacement of the spinal cord. Histological examination with immunohistochemical analysis of the epidural mass demonstrated a classic-type Hodgkin lymphoma. Early pathology-specific treatment allowed to avoid urgent surgery, achieve survival and restore of neurological function. Conclusions Children and adolescents with back pain and neurological abnormalities should be prioritized to avoid diagnostic delay resulting in potential loss of neurological function. SCC requires a prompt radiological assessment and an expert multidisciplinary management.